Faktor-Faktor yang Meningkatkan Prognosis Fetal dan Maternal pada Kehamilan dengan Kanker Ovarium - Imantika, Efriyan; Prawitasari, Shinta; Hadiati, Diah Rumekti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2019)
Background: Pregnancy complicated by ovarian cancer presents relation between controlled growth in pregnancy and uncontrolled growth in cancer. The management of pregnancy illustrate conflict between optimal maternal therapy and fetal life for best prognosis at all. The incidence was low but it occured in reproductive age women and most found in the first pregnancy. It is important to analyze factors that improve the prognosis of pregnancy and appropiate management to prevent fetal and maternal morbidity and mortality.Â Objectives: To analyze factor on pregnancy complicated by ovarian cancer that improve fetal and maternal prognosisMethods: This is descriptive analytic study with cohort retrospective design using medical records of pregnancy patient complicated by ovarian cancer that underwent treatment at Sardjito Hospital Yogyakarta on 2010, January till 2017, December. All statistical analysis were done by statistic software for computer.Results: There were 18 research subjek had been undergone treatment at Sardjito Hospital for 8 years. Factors on pregnancy related to prognosis of pregnancy complicated by ovarian cancer were late gestational age at the cancer diagnosis and epithelial histopathology type. That factors have better prognosis than early gestational age and non-epithelial histopathology clinically (p=0.18; CI 95% 0.4-104.2; OR 6,5) and (p=0.29; CI 95% 0.36-30.12; OR 3.28). Timing of surgery intervention improve prognosis of pregnancy statistically and clinically significant (p=0.02; OR=4.2).Â Conclusion: Factors on pregnancy complicated by ovarian cancer that is late gestational age at the cancer diagnosis, epithelial histopathology type and timing of surgery intervention type II-III improved fetal and maternal prognosis. Best management of pregnancy lead to better prognosis.Keywords: prognosis of pregnancy, ovarian cancer.Â